Isu Sosial dan Etika dalam Pemanfaatan ICT - Sonang Matua Siregar; Muhammad Irwan Padli Nasution (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Increasingly, every facet of society throughout the globe is concentrating on the advancement of information technology, often known as ICT (Information and Communication Technologies). We anticipate that human resource practices will evolve in tandem with information and communication technology. In this age of globalization, proficiency with ICT (Information and Communication Technology) is crucial. The ability to access, process, and display information via computers, whether it be an intranet, an international network, or the internet, is essential for many organizations and has grown in importance over the years. Since information and communication technology (ICT) has far-reaching societal effects, it naturally gives rise to ethical questions in many domains. This essay aims to help readers comprehend the role of education in reducing the detrimental effects of immoral use of information and communication technologies. Writing think about is the approach used. With more and more people becoming smarter in data and communication innovations, it's crucial that morality becomes a central tenet of how these technologies are used, and that the general public understands this.